Pengaruh Keterlibatan Pelanggan Dan Kepercayaan Merek Terhadap Loyalitas Merek Pada Pengguna Smartphone Xioami Di Kota Padang Dengan Kepuasan Pelanggan Sebagai Variabel Mediasi - lnzaghi, Dhani; Rahmidani, Rose (Jurnal Ecogen, 2024)
This study aims to analyze the effect of customer engagement and brand trust on brand loyalty in Xiaomi smartphone users in Padang City with satisfaction as a mediating variable. The population in the study were all people in Padang City who purchased Xiaomi smartphone 2 times. The determination of the number of samples using the Chochran formula. The number of samples in this study were 97 people using purposive sampling technique. The questionnaire was assessed using a Likert scale calculation. Data analysis techniques such as descriptive analysis, data verification, calculating the respondent's answer value and average. then SEM analysis with two stages in the form of measurement model testing used for validity and reliability tests and structural model testing used for causative tests. The data analysis tool used is SmartPLS 4.0. The results showed that (1) customer involvement has no positive effect on brand loyalty. (2) brand trust has a positive effect on brand loyalty. (3) customer involvement has a positive effect on customer satisfaction. (4) brand trust has a positive effect on customer satisfaction. (5) customer satisfaction has no positive effect on brand loyalty. (6) customer involvement has no positive effect on brand loyalty through customer satisfaction as a mediating variable. (7) brand trust has no positive effect on brand loyalty through customer satisfaction as a mediating variable